Replication of "Re-Assessing Elite-Public Gaps in Political Behavior" by Joshua Kertzer - Eric Guntermann; Gabriel S. Lenz (Institute for Replication (I4R), 2022)
Kertzer (2022) conducts a meta-analysis of parallel experiments on samples of political elites and ordinary citizens. He examines whether the average treatment effect for elites is significantly different from the average treatment effect for citizens, finding that only 19 of 162 (11.7%) difference-in-difference estimates are statistically significant after adjusting for the false discovery rate. He also finds that elites and masses hold similar foreign policy attitudes after controlling for their demographic characteristics. In this replication report, we begin by running robustness and heterogeneity tests for the first claim. We find that the results survive many robustness tests. We also find, however, that only a small number of the these treatments significantly affected masses (N=28) or elites (N=30). This low rate suggests the possibility that almost all of these experiments failed to successfully manipulate either masses or elites. If so, we may not be able to conclude that masses and elites respond similarly to experiments with confidence until political scientists produce more experiments with actual treatment effects or with successful manipulation checks in cases of null effects. In the second part of this replication report, we conceptually replicate the second Kertzer analysis, finding a strong correlation between elite and mass political decisions and attitudes, thus confirming Kertzer's analysis.
Keywords: 330